Driving performance enhancement using fuel cell in E-scooters - Unal, Sencer; Biyik, Hilal (Pergamon-Elsevier Science Ltd, 2024)
Today, fossil fuels used in urban transportation vehicles have great harm to the environment. In order to minimize these damages, the demand for transportation vehicles that use renewable energy sources is increasing day by day. Their high energy efficiency, zero emission values, not causing traffic congestion, saving time, no parking problems and being affordable have made the use of electric scooters (e-scooter) more advantageous than other means of transportation. Studies carried out to increase the performance of e-scooters, which have become popular in modern city life, are of great importance. With this study, we aimed to eliminate the problems encountered in electric scooters, such as short charging life of the battery, long charging times and most importantly, short driving range. For this purpose, a scooter simulation model was proposed in which a fuel cell, the energy source of the future, is used instead of a battery in an electric scooter. In addition, it is powered from the battery to be able to compare the results obtained and a scooter model with regenerative recovery was also realized. The dynamic behaviors of both models presented are compared for the first time according to long-term driving cycle conditions, and it is aimed to provide motivation to the researchers for future studies on this subject. In order to make the driving conditions more realistic in the simulation were chosen from the most popular inner city driving cycles, the European Economic Commission-15 (ECE 15), the Worldwide Harmonized Motorcycle Emissions Certification Procedure (WMTC) and the Assessment and Reliability of Transport Emission Models and Inventory Systems (ARTEMIS) Urban driving cycles. During these driving cycles, the performance of the scooter models was compared and the results were evaluated. From the results obtained from three different driving cycles, it is seen that a scooter designed using a fuel cell can provide over 120% increase in range compared to a battery scooter.
Keywords: Electric scooter; Hydrogen fuel cell; Lithium -ion (Li -ion) battery; Driving cycles